2022
DOI: 10.1093/cercor/bhac491
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in default mode network connectivity in healthy aging adults

Abstract: Women show an increased lifetime risk of Alzheimer’s disease (AD) compared with men. Characteristic brain connectivity changes, particularly within the default mode network (DMN), have been associated with both symptomatic and preclinical AD, but the impact of sex on DMN function throughout aging is poorly understood. We investigated sex differences in DMN connectivity over the lifespan in 595 cognitively healthy participants from the Human Connectome Project-Aging cohort. We used the intrinsic connectivity di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 111 publications
3
21
0
Order By: Relevance
“…Edges from connectivity matrices for each subject per scan were correlated to the three aforementioned memory performance measures, totaling to seven connectivity matrices and three memory scores per subject (21 total correlated matrices). Motion and age covariates were also included in the CPM analyses to account for in-scanner head motion, age, and their interaction in our predictions, as previously done (Scheinost et al, 2021;Dufford et al, 2022;Horien et al, 2022).…”
Section: Connectome-based Predictive Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Edges from connectivity matrices for each subject per scan were correlated to the three aforementioned memory performance measures, totaling to seven connectivity matrices and three memory scores per subject (21 total correlated matrices). Motion and age covariates were also included in the CPM analyses to account for in-scanner head motion, age, and their interaction in our predictions, as previously done (Scheinost et al, 2021;Dufford et al, 2022;Horien et al, 2022).…”
Section: Connectome-based Predictive Modelingmentioning
confidence: 99%
“…To visualize sex differences at the network level, we first split the aforementioned consensus matrix into two binarized matrices (a "positive" matrix containing edge with significant positive correlations to memory and the other "negative" matrix of edges with significant negative correlations to memory) for each predictive model. Categorization of nodes by functional network was determined using the 10-network parcellation of the Shen 268node atlas (Horien et al, 2022). In this network grouping, the medial frontal (MF) network also includes some temporal and frontal nodes which often cluster with the DMN.…”
Section: Inter-network Significant-edge Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…22 The FC of males and females is also quantitatively different, with females having higher intra-default mode network (DMN) connectivity and males having relatively greater connectivity between the DMN and other networks, although there is a wide degree of individual variation. 23,24 Meanwhile, studies have shown that changes occur in the DMN during late middle and old age, 25 although the exact direction of change in FC does not always appear constant. 26 In addition, various studies have examined age-related changes in the cingulum 27 and medial temporal lobe.…”
Section: Introductionmentioning
confidence: 99%
“…For example, connectivity in young children is generally very high among all brain regions and decreases while becoming more modularized during and after puberty 22 . The FC of males and females is also quantitatively different, with females having higher intra-default mode network (DMN) connectivity and males having relatively greater connectivity between the DMN and other networks, although there is a wide degree of individual variation 23 , 24 . Meanwhile, studies have shown that changes occur in the DMN during late middle and old age, 25 although the exact direction of change in FC does not always appear constant 26 .…”
Section: Introductionmentioning
confidence: 99%